2008
DOI: 10.1061/(asce)0733-9445(2008)134:1(3)
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dissipation Systems for Seismic Applications: Current Practice and Recent Developments

Abstract: This paper presents a summary of current practice and recent developments in the application of passive energy dissipation systems for seismic protection of structures. The emphasis is on the application of passive energy dissipation systems within the framing of building structures. Major topics that are presented include basic principles of energy dissipation systems, descriptions of the mechanical behavior and mathematical modeling of selected passive energy dissipation devices, advantages and disadvantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
245
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(294 citation statements)
references
References 52 publications
(26 reference statements)
1
245
0
7
Order By: Relevance
“…where c d is the damping constant; α is the velocity exponent that usually takes values between 0.15 and 1.0 for seismic applications and characterizes damper nonlinearity; d u  is the velocity across the damper; and sgn is the signum function [13].…”
Section: Simplified Nonlinear Structural Systems With Viscous Dampersmentioning
confidence: 99%
See 1 more Smart Citation
“…where c d is the damping constant; α is the velocity exponent that usually takes values between 0.15 and 1.0 for seismic applications and characterizes damper nonlinearity; d u  is the velocity across the damper; and sgn is the signum function [13].…”
Section: Simplified Nonlinear Structural Systems With Viscous Dampersmentioning
confidence: 99%
“…Rate-dependent passive dampers (viscous, viscoelastic, elastomeric; referred to herein as passive dampers) have been extensively used in seismic-resistant design and retrofit [13]. Lin and Chopra [14] studied highly damped elastic SDOF systems and showed that supplemental viscous damping is more effective in reducing displacements than total accelerations.…”
Section: Introductionmentioning
confidence: 99%
“…After 1989 Loma Prieta and 1994 Northridge earthquakes, using passive energy dissipation systems for seismic design of structures was developed increasingly [2]. The principle role of a passive energy dissipation system is to reduce the inelastic deformation demands on the framing system of a structure [3]. These systems absorb a significant amount of the input energy from earthquake to the structure.…”
Section: Introductionmentioning
confidence: 99%
“…These dampers improve seismic performance by absorbing earthquake force and reducing structural response. Among these passive energy dissipation systems, FVDs are nowadays extensively used for the seismic design of new structures and seismic rehabilitation of existing structures [3,6]. They can enhance the viscous damping of structures to more than 20-30% of critical damping (in addition to the inherent damping of structures) and decrease stresses and strains caused by the earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…A classical way to achieve this purpose is by designing ductile structures, as prescribed by seismic codes. Well-established techniques are also based on energy dissipaters inside the structure [1] or isolators at its base [2]. The principal feature of base-isolation techniques is, in fact, that of reducing stiffness, which is expected to reduce earthquake-induced accelerations.…”
Section: Introductionmentioning
confidence: 99%